U-shaped association of uric acid to overall-cause mortality and its impact on clinical management of hyperuricemia - William T. Crawley; Cyprien G. Jungels; Kurt R. Stenmark; Mehdi A. Fini (Redox Biology, 2022)
Serum uric acid (SUA) is significantly elevated in obesity, gout, type 2 diabetes mellitus, and the metabolic syndrome and appears to contribute to the renal, cardiovascular and pulmonary comorbidities that are associated with these disorders. Most previous studies have focused on the pathophysiologic effects of high levels of uric acid (hyperuricemia). More recently, research has also shifted to the impact of hypouricemia, with multiple studies showing the potentially damaging effects that can be caused by abnormally low levels of SUA. Along with these observations, recent inconclusive data from human studies evaluating the treatment of hyperuricemia with xanthine oxidoreductase (XOR) inhibitors have added to the debate about the causal role of UA in human disease processes. SUA, which is largely derived from hepatic degradation of purines, appears to exert both systemic pro-inflammatory effects that contribute to disease and protective antioxidant properties. XOR, which catalyzes the terminal two steps of purine degradation, is the major source of both reactive oxygen species (O2.-, H2O2) and UA. This review will summarize the evidence that both elevated and low SUA may be risk factors for renal, cardiovascular and pulmonary comorbidities. It will also discuss the mechanisms through which modulation of either XOR activity or SUA may contribute to vascular redox hemostasis. We will address future research studies to better account for the differential effects of high versus low SUA in the hope that this will identify new evidence-based approaches for the management of hyperuricemia.